The risk elicitation puzzle revisited: Across-methods (in)consistency? - Felix Holzmeister; Matthias Stefan (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2019)
With the rise of experimental research in the social sciences, numerous methods to elicit and classify people's risk attitudes in the laboratory have evolved. However, evidence suggests that people's attitudes towards risk may change considerably when measured with different methods. Based on a with-subject experimental design using four widespread risk preference elicitation methods, we find that different procedures indeed give rise to considerably varying estimates of individual and aggregate level risk preferences. Conducting simulation exercises to obtain benchmarks for subjects' behavior, we find that the observed heterogeneity in risk preference estimates across methods looks qualitatively similar to the heterogeneity arising from independent random draws from choices in the experimental tasks, despite significantly positive correlations between tasks. Our study, however, provides evidence that subjects are surprisingly well aware of the variation in the riskiness of their choices. We argue that this calls into question the common interpretation of variation in revealed risk preferences as being inconsistent.
Keywords: C91; D81; 330; Risk preference elicitation; inconsistent behavior; risk attitudes